2014
DOI: 10.1016/j.joca.2014.01.009
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a novel antibody to calcitonin gene-related peptide for the treatment of osteoarthritis-related pain

Abstract: LY2951742 is a high affinity, neutralizing antibody to CGRP. Neutralization of CGRP is efficacious in several OA pain models and works independently of NSAID mechanisms of action. LY2951742 holds promise for the treatment of pain in OA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 36 publications
6
88
0
2
Order By: Relevance
“…This is in agreement with the observation that several parts of the brain involved in pain transmission by the trigeminal nerve appear not to be protected by the BBB and are therefore potential targets of CGRP-R antagonists (Eftekhari et al, 2013). Additionally, should CGRP antibodies prove efficacious for the treatment of other chronic impairments, such as osteoarthritis (Mapp et al, 2012;Hirsch et al, 2013;Benschop et al, 2014) and menopausal flushing (Gupta et al, 2007;Hay and Poyner, 2009), the favorable dosing scheme of antibodies over small molecules could increase their therapeutic value. The first positive results from clinical proof-of-concept studies in migraine prevention with LY2951742 and ALD-403 were presented at the 2014 American Academy of Neurology conference, and additional clinical trials with LY2951742 (Bigal and Walter, 2014) and other antibodies to CGRP (LBR-101) or CGRP-R (AMG334) are underway.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This is in agreement with the observation that several parts of the brain involved in pain transmission by the trigeminal nerve appear not to be protected by the BBB and are therefore potential targets of CGRP-R antagonists (Eftekhari et al, 2013). Additionally, should CGRP antibodies prove efficacious for the treatment of other chronic impairments, such as osteoarthritis (Mapp et al, 2012;Hirsch et al, 2013;Benschop et al, 2014) and menopausal flushing (Gupta et al, 2007;Hay and Poyner, 2009), the favorable dosing scheme of antibodies over small molecules could increase their therapeutic value. The first positive results from clinical proof-of-concept studies in migraine prevention with LY2951742 and ALD-403 were presented at the 2014 American Academy of Neurology conference, and additional clinical trials with LY2951742 (Bigal and Walter, 2014) and other antibodies to CGRP (LBR-101) or CGRP-R (AMG334) are underway.…”
Section: Discussionsupporting
confidence: 86%
“…The results obtained with two different antibodies to CGRP (LSN2915644 and LY2951742) clearly demonstrated that both antibodies can effectively neutralize CGRP in vivo in animals for a prolonged period of time. We have previously reported the inhibition of capsaicininduced DBF in the rat using LY2951742 (Benschop et al, 2014). A similar method has been used by others to assess the target engagement of small molecule inhibitors of the CGRP receptor in the periphery in both preclinical (Hershey et al, 2005;Salvatore et al, 2008) and clinical (Salvatore et al, 2010;Sinclair et al, 2010) settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations